How do parents decide on genetic testing in pediatrics?: A systematic review - Doll, Elena Sophia; Lerch, Seraina Petra; Schmalenberger, Katja; Alex, Karla; Kölker, Stefan; Brennenstuhl, Heiko; Pereira, Stacey; Smith, Hadley S.; Winkler, Eva C.; Mahal, Julia; Ditzen, Beate (Genetics in medicine, 2025)
Purpose - This systematic review aims to identify the factors that influence parents’ decisions regarding pediatric diagnostic genetic testing (DT) and predictive genetic testing (PT). These factors are integrated into a conceptual decision-making model. Implications for genetic counseling, research, and ethics were derived. - Methods - PubMed, PsychInfo, WebofScience, and related references were searched for original publications between 2000 and 2023. The extracted factors were categorized using existing models. - Results - Of the 5843 publications, 56 met the inclusion criteria. The included studies differentiated between DT, traditional PT, and expanded PT and described factors affecting parental decisions to have the child genetically tested and to be informed about additional findings. Factors included (1) benefits/hopes, (2) worries/concerns, (3) values and beliefs, (4) individual circumstances, and (5) emotional states. - Conclusion - Our work extends the existing empirical decision model of family decisions about genome sequencing to genetic testing in pediatrics in general, adding the categories of individual circumstances and emotional states. These factors can be further integrated into the Health Belief Model; the importance of emotional states is reflected in dual-process theories, such as the Fuzzy Trace Theory. Research is required on emotional states, differences between DT and PT, parents’ decisions regarding result disclosure, and dyadic variables as decision-making predictors.